Monitoring marine pollution for carbon neutrality through a deep learning method with multi-source data fusion - Wang, Bin; Hua, Lijuan; Mei, Huan; Kang, Yanyan; Zhao, Ning (Frontiers in Ecology and Evolution, 2023)
Marine pollution can have a significant impact on the blue carbon, which finally affect the ocean's ability to sequester carbon and contribute to achieving carbon neutrality. Marine pollution is a complex problem that requires a great deal of time and effort to measure. Existing machine learning algorithms cannot effectively solve the detection time problem and provide limited accuracy. Moreover, marine pollution can come from a variety of sources. However, most of the existing research focused on a single ocean indicator to analyze marine pollution. In this study, two indicators, marine organisms and debris, are used to create a more complete picture of the extent and impact of pollution in the ocean. To effectively recognize different marine objects in the complex marine environment, we propose an integrated data fusion approach where deep CNNs are combined to conduct underwater object recognition. Through this multi-source data fusion approach, the accuracy of object recognition is significantly improved. After feature extraction, four machine and deep learning classifiers' performances are used to train on features extracted with deep CNNs. The results show that VGG-16 achieves better performance than other feature extractors when detecting marine organisms. When detecting marine debris, AlexNet outperforms other deep CNNs. The results also show that the LSTM classifier with VGG-16 for detecting marine organisms outperforms other deep learning models. For detecting marine debris, the best performance was observed with the AlexNet extractor, which obtained the best classification result with an LSTM. This information can be used to develop policies and practices aimed at reducing pollution and protecting marine environments for future generations.